Military autonomous robots and the responsibility for their use - Aziz, Peshraw Hama Jan; Khadr, Arazu Ahmad (Journal of Legal and Political Studies, 2022)
Military robots are one of the most modern types of weapons, having recently gained a prominent place in the armies of powerful countries as well as some third-world countries. Furthermore, robots are used in resolving issues raised by the use of this technology, such as how to implement the principle of global accountability for its role in conflicts and the extent to which criminal liability can be held. Similarly, military robots are unjustly held accountable for serious violations. The military robots are using a computerized database that is dependent on numerous programs. The programmer which intentionally directs this technology to commit war crimes and to set criminal combat targets, or the operator is the person who has the right of control and direction, on the other hand, abusing this technology or the commander is higher, because of the full commitment of these bots to the programs written for them, one can only accept human responsibility for their actions.
Keywords: Military robots; weapons; global accountability; criminal liability; human responsibility